#### Answer

$16x^{2}$ - 9$z^{2}$

#### Work Step by Step

(4x-3z)(4x+3z)=$(4x)^{2}$ - $(3z)^{2}$ =
=$16x^{2}$ - 9$z^{2}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$16x^{2}$ - 9$z^{2}$

(4x-3z)(4x+3z)=$(4x)^{2}$ - $(3z)^{2}$ =
=$16x^{2}$ - 9$z^{2}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.